Elderly in the state of co-residence in a town in State Bahia, Brazil - Sacramento Meira, Saulo; Benemérita Alves Vilela, Alba; Casotti, Cezar Augusto; Costa do Nascimento, Jorge; Barros Andrade, Camila (O Mundo da Saúde, 2015)
This study aims to describe the socioeconomic characteristics of the elderly and the level of individual and collective satis- faction in the structural and emotional aspects of family cohabitation. This is a cross-sectional, descriptive and exploratory household survey, by simple random sample, with individuals over 60 years, residents and enrolled in a health unit’s family in Jequié / BA and who has shown no cognitive impairment. Data were collected through a multidimensional question- naire Brazil Old Age Schedule (BOAS), tabulated and analyzed by Epi Info 3.3.2 program. We interviewed 154 individuals, 79.2% were female; 69.5% were illiterate; 39.6% ex-workers in the informal service and 41% widowed and living with an average of 3.8 people per household. As for monthly income, 84% live on minimum wage, 56% consider that their current income is sufficient for expenses and 80% consider themselves satisfied with life. The study elderly subjects are mostly female, with low education level, survive with up to one Brazilian minimum wage and consider themselves happy with life and with the other participants in co-residence. These data reveal that cohabitation has been satisfactory despite the low socioeconomic determinants of the elderly.